2008
DOI: 10.1002/pola.22867
|View full text |Cite
|
Sign up to set email alerts
|

Detitanation of MgCl2‐supported Ziegler‐Natta catalysts for the study of active sites organization

Abstract: Thermal treatments under vacuum of conventional supported Ziegler-Natta precatalysts (MgCl 2 /TiCl 4 /Dibutylphthalate) were conducted to gradually remove titanium to modify the active sites distribution. Only limited detitanations of precatalysts were achieved paying attention not to chemically alter the internal donor (T < 150 8C). Used in combination with the required cocatalyst and external donor in the propylene slurry polymerization, the modified precatalysts exhibited a drop of activity versus decreasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…Considering active sites at the precatalyst surface according to the “cluster” model,10 we aimed to modify their organization to change their properties (activity, selectivity). From this idea, we envisaged to replace some titanium atoms of clusters by another element.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering active sites at the precatalyst surface according to the “cluster” model,10 we aimed to modify their organization to change their properties (activity, selectivity). From this idea, we envisaged to replace some titanium atoms of clusters by another element.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that there exists no simple ways to separate the different families of active sites at the catalyst surface by various chemical or thermal modifications and thus to approach a “single‐site” behavior from a “multisite” catalyst 9, 10. From this observed collective behavior, we assumed a new model of active sites based on a “cluster” organization of titanium atoms at the catalyst surface 10…”
Section: Introductionmentioning
confidence: 99%
“…The commonly accepted roles [29][30][31][32] of the internal and external donors during the polymerization appear to be to bind to the (110) lateral cuts of MgCl 2 and thereby provide (i) stability to the more acidic, four-coordinate (110) MgCl 2 surfaces and (ii) stereoregulating control to active titanium catalysts adjacently bound to the same (110) MgCl 2 surface. Therefore, the manner in which the donor can bind to the MgCl 2 surface is a question of significance.…”
Section: Introductionmentioning
confidence: 96%
“…Spitz et al recently reported that internal donors might not have any direct role in the active site formation. [13] Thus, the role of internal donors for stabilizing MgCl 2 crystallites and blocking nonstereospecific/low-productivity sites became very critical.…”
Section: Introductionmentioning
confidence: 99%